PERAN DAN FUNGSI MODAL SOSIAL DALAM PENGEMBANGAN BANK PERBANKAN SYARIAH - Hasan, As'ari (JURIS (Jurnal Ilmiah Syariah), 2011)
Shariah Banks as Islamic financial institutions and as the indicators of Islamic economic strengths should not depend upon the power of Islamic emotions and capital only in their efforts to develop themselves. In fact, there are many things that they can do. One of which is by strengthening social capital, as what is believed by world funding boards, such as IMF and World Bank, in order to minimize crises and increase the economic condition of the community.